2014
DOI: 10.1007/s40258-013-0074-5
|View full text |Cite
|
Sign up to set email alerts
|

Managing Healthcare Budgets in Times of Austerity: The Role of Program Budgeting and Marginal Analysis

Abstract: Given limited resources, priority setting or choice making will remain a reality at all levels of publicly funded healthcare across countries for many years to come. The pressures may well be even more acute as the impact of the economic crisis of 2008 continues to play out but, even as economies begin to turn around, resources within healthcare will be limited, thus some form of rationing will be required. Over the last few decades, research on healthcare priority setting has focused on methods of implementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 31 publications
1
53
0
Order By: Relevance
“…The barriers, enablers and needs related to achieving the objectives are mapped to the relevant components of each intervention in Additional file 1. The findings of the local needs analysis are consistent with the current literature on EBDM using research and/or data [812, 15, 52, 62, 65, 91, 92], disinvestment and resource allocation [5659, 61, 64, 70, 76, 93–95], and information needs of health service decision-makers [39, 40, 43, 45, 53, 89]. More recently, systematic reviews have identified interventions that have been demonstrated to enhance uptake of research evidence and these are also included in the matrix [8, 67, 9699].…”
Section: Resultssupporting
confidence: 83%
“…The barriers, enablers and needs related to achieving the objectives are mapped to the relevant components of each intervention in Additional file 1. The findings of the local needs analysis are consistent with the current literature on EBDM using research and/or data [812, 15, 52, 62, 65, 91, 92], disinvestment and resource allocation [5659, 61, 64, 70, 76, 93–95], and information needs of health service decision-makers [39, 40, 43, 45, 53, 89]. More recently, systematic reviews have identified interventions that have been demonstrated to enhance uptake of research evidence and these are also included in the matrix [8, 67, 9699].…”
Section: Resultssupporting
confidence: 83%
“…Lack of transparency was reported in the earlier explorations of decision-making at Monash Health [39] and is also discussed in the literature in relation to disinvestment processes [7, 23, 62, 77, 83, 99, 135]. …”
Section: Resultsmentioning
confidence: 92%
“…The major limitations for all priority setting approaches include lack of standardisation in cost-accounting, lack of sufficient high quality data to inform decision-making, and lack of time and skills to undertake the process and implement the decisions [5, 9, 77, 78, 8385]. …”
Section: Resultsmentioning
confidence: 99%
“…Cost per DALY averted is the dominant measure of cost‐effectiveness, and it is often justified on the grounds that almost 90% of the global burden of disease is accounted for by LMICs (Murray and Lopez, ; Zarate, ). PBMA, which creates a management process into which results from standard economic evaluations and other evidence can be incorporated (Ruta et al, ), has been widely used in HICs including Australia, Canada, New Zealand and the UK (Mitton et al, ) but has not established a footing in LMICs. In addition to the widespread problem of a lack of credible information, the legitimacy and capacity of institutions management processes are often weak.…”
Section: Discussionmentioning
confidence: 99%